The Impact of Local Wisdom Education 'Poda Na Lima' on Community Knowledge in Dengue Infection Prevention - Daulay, Majidah Andilaila; Saragih, Rina Amalia Caromina; Rina Amelia; Pasaribu, Ayodhia Pitaloka; Fithri Hervianti; Veralia (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2025)
Background. Dengue remains an endemic disease in almost all countries worldwide, including Indonesia. One approach to its prevention and control is community empowerment through education. Education is most impactful when aligned with the culture and local wisdom of the target community. Poda na lima is a form of local wisdom practiced by the Batak Angkola-Mandailing tribe in North Sumatra Province, Indonesia. This study aims to analyze the effect of poda na lima-based education on community knowledge regarding dengue prevention. Methods. Quasi-experiment with one group pretest-posttest. This study involved 68 respondents from the community in the working area of Puskesmas Sihepeng, Mandailing Natal Regency, through cluster random sampling with inclusion criteria in October – November 2024. Data were collected using questionnaires before and after the dengue education intervention with poda na lima and analyzed using the Wilcoxon signed rank test with the SPSS software. Result. Most of the respondents were in the age range of 19 – 45 years (80.9%), with a female gender (100%) and an education level of high school graduate (39.7%). There was an increase in the average knowledge before and after dengue education with the poda na lima, with statistically significant results (p<0.05) and an effect size > 0.5, meaning that the dengue education with the poda na lima has a large effect on the improve in knowledge. Conclusion. Dengue education with local wisdom poda na lima has a significant and large effect on improving community knowledge.